Multi-level analysis of visitors’ satisfaction flying to Debrecen – main aspects of the research - Palatinus, Brigitta (Applied Studies in Agribusiness and Commerce, 2015)
This paper presents the non-exhaustive description of the main characteristics of visitors based on the filled out questionnaires during five months following the test month. These characteristics will serve the basis of a satisfaction analysis to be described in the future and they provide guidance for later analyses. I performed the testing of my questionnaire in January 2014. It turned out even from the data collected in the test phase that there were services which did not meet the expectations of visitors several times as it was worse than what they expected. This study focuses on the questionnaire research conducted among foreign visitors coming to Debrecen by flight. The main aspects were to determine foreign visitors purpose of travel to Debrecen, how many times they had already been to Debrecen, how many days they spent in the city, what kind of services did they use and whether the quality of used service met their expectations. As a result of the following five months research, I obtained input data which make it possible to examine real problems with background data. It calls for further examination to determine whether there was any difference in the extent of services living up to visitors’ expectation and visitors’ level of satisfaction.